Are family‐friendly workplace practices a valuable firm resource? - Bloom, Nick; Kretschmer, Tobias; Van Reenen, John (Strategic Management Journal, 2011)
We study the determinants and consequences of family‐friendly workplace practices (FFWP) using a sample of over 450 manufacturing firms in Germany, France, U.K., and U.S. We find a positive correlation between firm productivity and FFWP. This association disappears, however, once we control for a measure of the quality of management practices. We further find that firms with a higher proportion of female managers and more skilled workers, as well as well‐managed firms, tend to implement more FFWP. Conversely, a firm's environment does not have a significant impact on the FFWP it provides. © 2010 The Authors. Strategic Management Journal published by John Wiley & Sons, Ltd. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.